Autophagy as an emerging therapy target for ovarian carcinoma - Zhan, Lei (Oncotarget, 2016)
Autophagy is a conserved cellular self-digestion pathway for maintenance of homeostasis under basal and stressed conditions. Autophagy plays pivotal roles in the pathogenesis of many diseases, such as aging-related diseases, autoimmune diseases, cardiovascular diseases, and cancers. Of special note is that accumulating data suggest an intimate relationship between autophagy and ovarian carcinoma. Autophagy is well identified to act as either as a tumor-suppressor or as a tumor-promoter in ovarian carcinoma. The exact function of autophagy in ovarian carcinoma is highly dependent on the circumstances of cancer including hypoxic, nutrient-deficient, chemotherapy and so on. However, the mechanism underlying autophagy associated with ovarian carcinoma remains elusive, the precise role of autophagy in ovarian carcinoma also remains undetermined. In this review, we tried to sum up and discuss recent research achievements of autophagy in ovarian cancer. Moreover, waves of novel therapies ways for ovarian carcinoma based on the functions of autophagy were collected.